Considering a New Call: Ethical and Spiritual Challenges for Clergy - Antal, James M., (Rowman & Littlefield Publishers, 2000)
Serving faithfully in one's current congregation while simultaneously going through the secretive process of looking for a new position is one of the most difficult dilemmas of any pastor's life. How should one respond to 'getting the itch'? Where is the line between keeping confidentialities and presenting one's credentials in the most favourable and realistic light? What are the consequences of being an active candidate? Antal's companionable approach stimulates theological and spiritual reflection on matters of the most practical consequence, promotes self-understanding, and enhances ministry.